Telecommunication Submarine-C able Deployment and the Digital Divide in Sub-Saharan Africa - (:unkn) unknown (My University, 2018)
This paper estimates the impact of fiber-optic submarine cables (SMCs) deployment on the digital divide in 46 sub-Saharan African (SSA) countries. It shows that the laying of SEACOM, MainOne and EASSy cables has yielded a 3-4% point increase in internet penetration rates. Moreover, it also shows that the reduction in landlocked countries’ digital isolation, following the laying of SMCs, has boosted Internet access and reduced telecommunication disruptions. Finally, it stresses that the arrival of SMCs may increase countries’ vulnerability to SMC faults, by showing how SMCs exposure to seismic risk lowers Internet and mobile penetration rates, and increases telecommunication disruptions.
Keywords: African Research